2023
DOI: 10.1101/2023.01.17.524469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Systematic Survey of Reversibly Covalent Dipeptidyl Inhibitors of the SARS-CoV-2 Main Protease

Abstract: SARS-CoV-2 is the coronavirus pathogen of the currently prevailing COVID-19 pandemic. It relies on its main protease (MPro) for replication and pathogenesis. MPro is a demonstrated target for the development of antivirals for SARS-CoV-2. Past studies have systematically explored tripeptidyl inhibitors such as nirmatrelvir as MPro inhibitors. However, dipeptidyl inhibitors especially those with a spiro residue at their P2 position have not been systematically investigated. In this work, we synthesized about 30 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Proline-based P2 residues, which induced higher structural rigidity, have frequently been embedded in peptidomimetic M pro inhibitors. 11,12 We incorporated proline in case of 73, which was accompanied by the complete loss of activity, in agreement with the results obtained for azanitriles with other cyclic P2 amino acids (61, 62; Table 2). X-ray Crystal Structure Analyses and Molecular Design of Macrocyclic Azanitriles.…”
Section: ■ Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Proline-based P2 residues, which induced higher structural rigidity, have frequently been embedded in peptidomimetic M pro inhibitors. 11,12 We incorporated proline in case of 73, which was accompanied by the complete loss of activity, in agreement with the results obtained for azanitriles with other cyclic P2 amino acids (61, 62; Table 2). X-ray Crystal Structure Analyses and Molecular Design of Macrocyclic Azanitriles.…”
Section: ■ Introductionsupporting
confidence: 86%
“…For this purpose, Cbz-phenylalanine occupying the S4−S2 subsites was used and a phenyl ring as part of the P1 unit was subjected to a systematic halogen scan (1−23) or replaced by furan and thiophene (24 and 25). We also considered (S)-3-methylpyrrolidine-2-one, the most frequently used glutamine mimetic in peptidic M pro inhibitors, [9][10][11][12]37,38 and synthesized compound 26, which contained 3-methylpyrrolidine-2-one as a racemic unit.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As such, various P1 substitutions other than the pyrrolidone such as pyridine or pyrimidine need to be explored . Q189, M49, H41, and M165 are key residues forming the S2-binding pocket (Figures b and ), and corresponding P2 substitutions such as spiroproline can be considered for inhibitor design . Additional consideration for the design of M pro inhibitors with a high genetic barrier to drug resistance is to fit inhibitors within the substrate envelope …”
Section: Resultsmentioning
confidence: 99%
“…31 Q189, M49, H41, and M165 are key residues forming the S2-binding pocket (Figures 1b and 5), and corresponding P2 substitutions such as spiroproline can be considered for inhibitor design. 32 Additional consideration for the design of M pro inhibitors with a high genetic barrier to drug resistance is to fit inhibitors within the substrate envelope. 19 ■ CONCLUSIONS Collectively, our results have several implications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Earlier crystallography research indicated that the N-indole-2carboxyl protection group in dipeptide M Pro inhibitors produced a hydrogen bond between the indole nitrogen and the M Pro E166 backbone carbonyl oxygen. 49 Both factors may contribute to the strong potency of MPI83 and MPI84. MPI90 was also developed to investigate if an azaconjugated -ketoacyl, specifically here as a pyruvoyl group, could serve as a covalent warhead to react with the M Pro catalytic cysteine.…”
Section: Figure 1 (A)mentioning
confidence: 99%